Teknik Relakasasi Air Hangat Pada Pasien Gastritis - Putri, Suhartania Dwi; Hardono, Hardono; Wahyudi, Dian Arif (Wellness And Healthy Magazine, 2021)
Introduction: Gastritis is also known as heartburn; it is an inflammation (swelling) of the gastric mucosa caused by irritation and infection. The various studies conclude that the most common pain complaints in gastritis are due to functional gastritis, which reaches 70-80% of all cases, which is a disease that is not caused by disorders of the stomach organs, but it is more often triggered by inappropriate dietary, psychic factors and anxiety (Saydam, 2015). Research Objective: Obtain real experience in carrying out nursing care for patients diagnosed with gastritis. Methods: Assessment, Nursing Diagnosis, Determination of Nursing Plans, Implementation of Nursing Actions, and Evaluation. Results: The results obtained that after nursing care for patients with the diagnosis of gastritis, the researchers received a nursing diagnosis that appeared, namely chronic pain associated with physiological injury agents (inflammation, sleep disorders related to the effects of pain, the risk of nutritional deficits related to the psychological factors (reluctance to eat). Conclusion: After nursing care for the patient for three days, there was a change in the condition to be better, pain disappeared after warm water compresses, sleep and eating patterns became regularly.